Discrete Electronic Load Controller for minimizing Total Harmonic Distortion in Micro Hydro Power Plants - Poudel, Bishal; Bimal Poudel,; Suraj Shrestha,; Sandip Dhami,; Hari Sharan Dangi, (Journal of Innovations in Engineering Education, 2024)
Micro hydropower systems have emerged as crucial contributors to sustainable energy in remote areas, bringing forth the need for meticulous integration into power grids. Total Harmonic Distortion (THD) stands as a pivotal metric, with elevated levels leading to inefficiencies, equipment degradation, and operational challenges. This abstract presents an innovative approach to tackle this issue by employing a Discrete Electronic Load Controller (DELC) within the realm of multiple Micro hydro power Plants (MHPP). In pursuit of optimizing power quality and operational efficiency, the primary objective of this research is to develop and implement an advanced control strategy utilizing DELC to minimize THD in systems with multiple MHPPs. The comprehensive methodology encompasses an exhaustive literature review, system characterization, DELC design, simulation and modeling in MATLAB, and optional hardware implementation, thus, the obtained performance evaluation involves a thorough comparison between the proposed DELC and conventional control strategies and the simulation results showcase the remarkable reduction in THD achieved by the DELC, validating its efficacy over traditional control methods. An iterative process optimizes Proportional-Integral-Derivative (PID) parameters, ensuring minimal THD while maintaining system stability. Robustness testing involves scenarios with various faults and load variations, affirming the robustness of the proposed DELC strategy. This research contributes significantly to sustainable energy endeavors by demonstrating the effectiveness of DELC for THD minimization in multiple MHPPs. Beyond enhancing power quality, the optimized control strategy fortifies system stability, positioning micro hydropower as a reliable energy source for seamless integration into broader power grids. Looking ahead, future investigations could delve into the scalability and adaptability of the proposed DELC strategy for diverse micro hydropower configurations and network conditions. Additionally, assessing the economic feasibility and long-term performance of DELC-controlled MHPP systems will be instrumental for comprehensive insights into sustainable energy solutions. This research provides valuable guidance for the ongoing evolution of microhydropower systems in the quest for sustainable and efficient energy sources.